The Effect of Finger Painting Therapy on Preschool Children’s Language and Fine Motor Development - Jamilah, Jamilah; Mujahid, Ikhsan (Proceedings Series on Health & Medical Sciences, 2024)
Background: Insufficient stimulation in children might lead to deficits in fine motor development. Young children must improve their language skills so they can orally express what is on their minds and help others comprehend what they desire. Activities like finger painting help improves creativity, imagination, eye, muscular, and brain coordination, and color blending abilities. Method: Quantitative pre-experimental study with one group pretest and posttest design. The population and sample used were 41 respondents with the total sampling method. The statistical test used is the Wilcoxon test. Results: The findings showed that the respondents’ fine motor development in the normal category was 56.1% before therapy and that it climbed to 97.6% after receiving therapy. The results of the respondent’s language development were 51.2% before therapy in the normal category, and it increased to 90.2% after receiving developmental therapy in the normal category. Conclusion: There is an effect of finger painting therapy on fine motor development and language development in preschool-aged children.